Thoracic Endovascular Aortic Repair (TEVAR): A Case Report (Bangladesh Heart Journal, 2019)
Thoracic aortic aneurysm (TAA) is generally a disease of the elderly which remains mostly asymptomatic. It is often detected incidentally with imaging studies of the chest done for other reasons. We present a 55year-old smoker, normotensive and non-diabetic male patient who was diagnosed as a case of TAA and treated by endovascular means with thoracic endovascular aortic repair (TEVAR) technique. Due to small caliber femoral artery, thoracic endograft was deployed through a Dacron graft conduit of 10 mm diameter which was anastomosed to the common iliac artery. It was a hybrid procedure done in cardiac catheterization laboratory under general anesthesia. Completion angiogram revealed good technical success with no endoleak or neurological deficit. Patient improved symptomatically after TEVAR.Bangladesh Heart Journal 2019; 34(2) : 146-150